KATA KETERANGAN DALAM ALBUM â€œAFTER LAUGHTERâ€ DARI GRUP BAND PARAMORE - MANDANG, REFINA GABRIELA; KODONG, FENTJE; SENDUK, ARTER JODI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research entitled â€œAdverbs in Album After Laughter of Paramore Group Bandâ€ is written to fulfill the requirement of finish S1 degree in English Department Faculty of Letters Sam Ratulangi University. The aims of research are to indentify, classify and analyze the types and function of the adverbs found in the album of after laughter.The method use is descriptive method. The result of shows that the types ofÂ  adverb is the album After Laughter are: adverbs of manner, adverbs of place and direction, adverb of time, intensifying adverbs, sentence adverbs, conjuctive adverbs Â the functions of the adverbs are: adverb as modifier of a verb, adverb of adjectives and adverbs and adverb as modifier of the whole sentence. it is expected that this research contribute to linguistic theory in syntax and help student to understand more about adverbs.Â Key Words: Adverbs,Types and Functions, After Laughter.